Cherry blossoms after winter. 1 - Bamwoo (Bamwoo. Cherry blossoms after winter ;, 2024)
Despite growing up together, these childhood friends have grown apart. The fan-favorite boys' love manhwa turned K-drama comes to print for the first time. Seo Haebom was seven years old when his parents died in an accident. With nowhere else to go, he moves in with the family of his childhood friend Jo Taesung, who suddenly grows cold and distant, destroying their friendship. Now it's their senior year of high school and, after years of barely speaking to each other, Haebom and Taesung are in the same class for the first time. Haebom struggles to make friends and is plagued by bullying, but after the handsome and popular Taesung fends off his most persistent bully, everything changes--they sit together at lunch and begin to act like friends again. Haebom is unsure what to make of the shift, but this could be his last chance to mend their relationship.--